2017
DOI: 10.1007/s00238-016-1261-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of anthropomorphic measurements in implant selection for breast reconstruction: a retrospective cohort study

Abstract: Background Preoperative implant planning for breast reconstruction is often at risk of being changed perioperatively. This study examined which factors are associated with a change of implant selection. Methods Women who had unilateral two-stage breast reconstruction between 2002 and 2007 were studied. Inclusion criteria were photographic evidence of preoperative skin markings indicating breast dimensions and a selected implant model. Multivariable logistic regression was used to identify variables associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…All anthropometric volume measures of the breast are complex to perform and always represent estimates 29–34 and volume measures using 3D scans likewise. When used appropriately for 3D simulation, volume estimates can, however, be accurate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All anthropometric volume measures of the breast are complex to perform and always represent estimates 29–34 and volume measures using 3D scans likewise. When used appropriately for 3D simulation, volume estimates can, however, be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…28 The plastic surgeons felt almost as comfortable evaluating 3D scans as with performing clinical examinations. 7 All anthropometric volume measures of the breast are complex to perform and always represent estimates [29][30][31][32][33][34] and volume measures using 3D scans likewise. When used appropriately for 3D simulation, volume estimates can, however, be accurate.…”
Section: Limitationsmentioning
confidence: 99%
“…In this study, NAC to inferior mammary fold and breast projection were found to be significantly associated with breast attractiveness, while base diameter was not. 20 The base diameter is relatively easy to measure and has been shown by Riggio et al 21 to change less often from preoperative planning to intraoperative decision in implant breast reconstruction. On the other hand, base diameter is used frequently in clinical practice to assist in choice of implant.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were taken on the day before surgery to guide the reconstruction process. 10,11 After mastectomy, intraoperative assessment of flap viability was crucial, requiring close collaboration with the breast surgeon. Only well-perfused skin flaps allowed for immediate prepectoral reconstruction.…”
Section: Methodsmentioning
confidence: 99%